(untitled) (Journal of actual problems of jurisprudence, 2016)
Initially, the economic cooperation between Kazakhstan and Uzbekistan have developed quite successfully. This is confirmed by statistical data. For the post-Soviet history of bilateral economic relations greatest volume of trade recorded in 1992. According to the Executive Committee of the Interstate Council of Kazakhstan, Kyrgyzstan and Uzbekistan, in this year the trade turnover between Kazakhstan and Uzbekistan reached a record level of 2.6 billion USD. At the same time Kazakhstan’s exports to Uzbekistan amounted to 15.2% of turnover with the CIS countries, and imports of Uzbek goods in Kazakhstan – 12.9%. Қазақстан мен Өзбекстанның экономикалық байланыстары олардың тәуелсіздікке қол жеткіз геннен соң жандана бастады. Екі мемлекет бүгінгі таңға дейін көптеген халықаралық шарттарға қол қойған. Соның бірі екі ел үшін де аса маңызды экономикалық қатынастар болып есептеледі. Мақа лада қазақ-өзбек экономикалық қарым-қатынастарының жан-жақты аспектілері зерттелген. Олар нақты сандармен көрсетілген.